Climate change impacts on river discharge to the Sea of Marmara - Basdurak, Berkay Nüvit (Frontiers in Marine Science, 2023)
The Sea of Marmara, located in Northwestern Türkiye, is under multiple stressors, including climate change and industrial, agricultural, and domestic pollution, that cause deoxygenation in coastal waters, with multiregional consequences affecting the surface and deep-water masses transported to the Mediterranean and Black Seas, respectively, via its straits. With climate-change driven changes in the intensity of extreme precipitation events, the marine environment becomes more vulnerable to increasing terrestrial pollutants. Evaluating the spatial and temporal variation of river runoff is crucial to understanding the interaction between the geophysical and hydrogeochemical processes that affects the nutrient balance of the sea. This study aims to (i) explore the historical (for the period 1960-2021) and spatial changes of monthly-averaged coastal discharges along the coastline of the Sea of Marmara for the first time, based on observations from the national hydrological service; (ii) analyze the change in long-term and seasonal trends of runoff and net-precipitation rate and derive a regional relation between the two parameters. Single Spectrum Analysis (SSA) is used to obtain the trends. Gaps in the time series are filled in using a non-parametric spectral estimation method. Discharges from the northern, eastern, and southern basins are, respectively, 3%, 17%, and 80% of the total discharge, which has varied between 1.5 and 15 km3 per year in the last decade, with short-lived extremes occurring in early spring. Total runoff rate shows a declining long-term trend that is accelerating with increasing evaporation. The intensity of the terrestrial precipitation extremes shows a temporal increase; there is a quadratic relation between the long-term trends of net precipitation and total runoff. Quantification of nutrient load distribution along the coastline associated with the spatial-temporal changes in coastal fluxes is urgent because the cumulative stressors (warming, nutrient overenrichment, pollutants) pose a threat of triggering extreme events and eutrophication in the Sea of Marmara with multiregional impact.